Pengaruh Media Video Edukasi dan Website terhadap Pengetahuan Masyarakat Dewasa mengenai Diabetes Mellitus - Zahra Anisa Nurfalah; Ratih Kurniasari (LPPM Universitas Respati Indonesia, 2022)
Diabetes Mellitus or commonly called DM is a disease with chronic metabolism known as the silent killer and has blood glucose levels above normal. The active role of the community is the main key to success in reducing mortality due to DM. The purpose of this study was to determine the effect of educational media on knowledge of diabetes mellitus through educational videos and websites for adults. This study used a quasi-experimental research type with a pretest and post-test design with a control group design. The research subjects of the Purwakarta community aged 20-50 years, totaling 40 people with 2 intervention groups received education through educational videos and websites. The results showed the average value of public knowledge after and before being given education for the educational video group, the average value of knowledge before education (6.75) and after education (8.90) and for the knowledge website group before education (7.25). and after education (8,55). The conclusion in this study is that there is an effect of education using educational video media and websites on increasing public knowledge. So that this media can be used as a medium of education for the community.